STRATEGIES OF DEALING WITH CRISIS MANAGEMENT IN EDUCATIONAL INSTITUTIONS IRAQ SCHOOLS AS A MODEL - Ahmed Hameed Kareem Al Kalkawi (Scholar Express Journals, 2022)
The aim of this study is to identify the strategies of dealing with the educational crises and ow to face them and reaching at the suggested procedures of encountering the crises in the education schools in Iraq. The researcher has depended on the descriptive methodology, through preparing an open form of screening for the headmasters of five schools in Iraq to recognize the most important strategies of facing the management of the educational crisis. The researcher arrived at a suggested perception for the management of the educational crises in the schools of Iraq represented by discovering the initial signals alarm of anticipating the educational crisis, reducing the intensity of it and full preparation to face it, facing the educational crisis, planning for managing the educational crisis, and planning in dealing with the crisis. As for the proposed vision for activating strategies to confront the educational crisis in Iraqi schools, it was represented in providing an information database that helps in managing educational crises, as well as holding training courses for Iraqi school workers in the field of crisis management,Establishing a crisis management unit in schools, the necessity of adopting modern methods in dealing with crises if they occur, community participation and involving parents and the community in school meetings, and developing plans to confront crises.
Keywords: educational crises; education schools